Evaluasi Kelayakan Modul Mata Kuliah Profesi Kependidikan Berbasis Pembelajaran Kasus - Masyhud, Masyhud; Fitriani, Fitriani (Lembaga Publikasi Ilmiah Nusantara, 2025)
A high-quality learning module plays a crucial role in enhancing the effectiveness of the teaching and learning process, especially in the Educational Profession course. This study aims to evaluate the feasibility of a module for the Educational Profession course developed using a case-based learning approach. This approach was chosen to improve students' understanding and skills in analyzing and solving real-world problems in the field of education. The study employs a Research and Development (R&D) method with an evaluation model involving subject matter experts, media experts, and limited trials with students. The instruments used in this study include questionnaires and observation sheets to assess the feasibility of the content, design, and applicability of the module in the learning process. The results show that the developed module received a